Prolonged hospitalisation for immigrants and high risk patients with positive smear pulmonary tuberculosis - Luzzati, R.; Confalonieri, M.; Cazzadori, A.; Della Loggia, P.; Cifaldi, R.; Fabris, C.; Biolo, M.; Borelli, M.; Longo, C.; Concia, E. (Monaldi Archives for Chest Disease, 2015)
Background and objective. Tuberculosis (TB) occurring in immigrants and resistance to drugs are major problems for TB control in Western countries. Directly observed therapy (DOT) reduces disease transmission, but this approach may have poor results among illegal immigrants. Our aim was to evaluate a prolonged hospitalisation programme to improve early outcome of TB treatment in high risk patients. Methods. All the consecutive adult patients with sputum smear-positive pulmonary TB admitted to 2 Italian referral TB Centres were evaluated. Hospital-based DOT was provided to high risk patients up-to smear conversion. Demographic, microbiological and clinical conditions, as potential factors associated with confirmed smear conversion at 60 and 90 days of anti-tuberculous therapy were evaluated. Results. 122 patients were studied, 45.9% of them were immigrants (20% illegal) from high-prevalence TB countries. HIV testing was negative in all cases. Twelve patients had M. tuberculosis resistant to â‰¥ 1 first-line anti-tuberculous agents. The rate of defaulting from TB treatment was 7.3%. Sputum smear became negative in 84.4% cases after 60 days and 93.3% cases after 90 days. At such time, smear conversion rates were similar among different high risk subgroups such as illegal immigrants (95.9%), legal foreign-born (92.5%) and Italian persons (94.8%). Persistent sputum smear positivity was independently correlated with the extent of pulmonary lesions at 60 (p<0.0001) and 90 days (p=0.038) of hospital-based DOT. Conclusions. These findings suggest that prolonged hospitalisation for illegal immigrants and high risk TB patients, may positively influence the early outcome of TB treatment despite of drug resistance and legal status.